2014
DOI: 10.1007/s00259-014-2864-x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of a new protocol for the provisional use of perfusion imaging with exercise stress testing

Abstract: A provisional injection protocol has a very low mortality, few follow-up diagnostic tests, and lower cost compared to standard imaging protocols. If adopted it would decrease radiation exposure, save time and decrease health-care costs without jeopardizing prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…In this issue of the Journal Smith and colleagues present the results of a study which supports one approach to layered testing which may improve the PPV of stress SPECT MPI. This work extends prior studies from Bourque 6,7 and Duvall 8,9 which showed that patients with excellent exercise capacity (C 10 METS) without concerning EKG changes or symptoms can safely omit radiotracer injection and imaging. The present work shows that this strategy is probably safe even among older adults C 65 years.…”
Section: What Is the Solution?supporting
confidence: 83%
“…In this issue of the Journal Smith and colleagues present the results of a study which supports one approach to layered testing which may improve the PPV of stress SPECT MPI. This work extends prior studies from Bourque 6,7 and Duvall 8,9 which showed that patients with excellent exercise capacity (C 10 METS) without concerning EKG changes or symptoms can safely omit radiotracer injection and imaging. The present work shows that this strategy is probably safe even among older adults C 65 years.…”
Section: What Is the Solution?supporting
confidence: 83%
“…With the advent of SPECT/CT cameras, the role of gated SPECT to identify attenuation artifacts has virtually disappeared due to the excellent attenuation correction with CT. This enables stress-only imaging in the majority of patients with normal perfusion findings that also confers an excellent cardiovascular outcome [6,7]. Since in the current investigation [1] no attenuation correction of CZT images was performed, myocardial perfusion imaging in conjunction with wall motion analysis most likely was needed in a certain number of patients to avoid false-positive findings due to attenuation artifacts, in particular in obese individuals and women [8].…”
mentioning
confidence: 97%
“…18 In a prospective study, they demonstrated that the application of this protocol is feasible and that patients who do not undergo imaging have a low rate of events during follow-up. 19 These studies show that the adoption of innovative protocols that avoid imaging altogether in select populations is safe, cost effective, and decreases radiation exposure.…”
mentioning
confidence: 99%